Story Games and the OPIATE System: Using Case-Based Planning for Structuring Plots with an Expert Story Director Agent and Enacting them in a Socially Simulated Game World - Fairclough, Chris (University of Dublin, Trinity College. Department of Computer Science, 2004)
Storytelling in computer games has become a major selling point for new titles. With new games integrating compelling storylines with simulated worlds, there is increasingly a standard set of techniques used to tell a story in games, including cut scenes, story-based missions, and the unlocking of new areas of exploration with successful goal completion. To further integrate story telling with the game play of future games, this work draws on storytelling methods in games, along with academic AI techniques and simulation methods, to propose an innovative paradigm for storytelling in future games. This thesis presents a new approach to creating game mechanics, utilising a number of key concepts that result in an interaction scheme that engages a player with a story, while allowing the player the freedom to interact with and alter that story as it happens. A story director agent was developed that uses case-based planning of skeletal plot scripts, modelled on Propp's morphology, and the dynamic adaptation of these plans. This agent was incorporated into a social simulation engine that a player interacts with through controlling one of the characters therein. The story director and social simulation are symbiotically linked, with a feedback mechanism that ensures plots are planned consistently with the simulation. The system was evaluated and analysed and has proved to represent a successful storytelling paradigm, implementing a high level of player interactivity with plotting, while providing an experience that takes the form of an organically whole storyline.
Keywords: Computer Science